Morus alba L. Leaf Extract Exerts Anti-Inflammatory Effect on Paraquat-Exposed Macrophages - Srinontong, Piyarat; Kathanya, Juthamanee; Juijaitong, Poonthariga; Soontonrote, Kanchanok; Aengwanich, Worapol; Wandee, Jaroon; Peanparkdee, Methavee; Wu, Zhiliang (Trends in Sciences, 2022)
Paraquat (PQ) is a widely used herbicide in agricultural areas. However, it has been reported to cause harm to animals or humans exposed to this herbicide. Generally, PQ stimulates the production of reactive oxygen species within cells causing cell death and resulting in bodily abnormalities. At present, efforts are being made to find drugs to reduce the toxic effects of PQ and natural products are targets of interest. This study aimed to assess the effect of mulberry (Morus alba L.) leaf extract on macrophages (RAW 264.7) after exposure to PQ, including the viability and expressions of NF-κB, IL-1β, and IL-6. We treated RAW 264.7 macrophages with Morus alba L. leaf extract in the absence or presence of PQ. Subsequently, viability, apoptosis, and expressions of NF-κB, IL-1β, and IL-6 were examined. It was found that the extract of mulberry leaves could inhibit apoptosis, increase viability, and significantly downregulates expressions of NF-κB, IL-1β, and IL-6 when RAW 264.7 macrophages were exposed to PQ. These phenomena indicated that Morus alba L. leaf extract has properties to reduce the inflammatory effect caused by the herbicide PQ. HIGHLIGHTS Morus alba L. leaf extract improved the PQ-induced apoptosis of RAW 264.7 macrophage Morus alba L. leaf extract inhibited the expression of NF-κB, IL-1β, and IL-6 of RAW 264.7 macrophages GRAPHICAL ABSTRACT